2021
DOI: 10.36472/msd.v8i9.604
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin K1 on VEGF levels in chick embryos with type 1 diabetes and Diabetic Retinopathy induced by streptozotocin

Abstract: Objective: Hyperglycemia caused by Diabetes Mellitus (DM) is associated with long-term dysfunction such as diabetic retinopathy (DRP). The most effective growth factor in the development of DRP is the vascular endothelial growth factor (VEGF). Vitamin K1 reduces hyperglycemia and prevents the development of DM. In this study, we aimed to create streptozotocin (STZ) induced DM and DRP in chick embryos and to show whether vitamin K1 can prevent early-stage DRP by measuring VEGF levels. Material and Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…The efficacy of circulating vitamin K has been successfully demonstrated worldwide in various clinical-based and population-based studies. In previous studies, it has been shown that dietary vitamin K1 reduces risk of type 2 DM and hyperglycemia [13,14]. Therefore, in this study, we aimed to immunohistochemically and morphologically examine vitamin K1 in STZ-induced chick embryo type 1 DM model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The efficacy of circulating vitamin K has been successfully demonstrated worldwide in various clinical-based and population-based studies. In previous studies, it has been shown that dietary vitamin K1 reduces risk of type 2 DM and hyperglycemia [13,14]. Therefore, in this study, we aimed to immunohistochemically and morphologically examine vitamin K1 in STZ-induced chick embryo type 1 DM model.…”
Section: Discussionmentioning
confidence: 99%
“…The dose of 0.30 mg/egg STZ was determined according to the literature to induce diabetes in chick embryos [10,15,16]. Three different doses vitamin K1 (Konakion 10 mg/ml, Roche) were administered for treatment [13].…”
Section: Chemicals and Dosesmentioning
confidence: 99%
See 1 more Smart Citation